(3eHOC MhceI GdHfhc WHbG dGJaGbjI HGRd GdOhdjI hCKQg Ydi GdbWGYjf GdeUQaj hGdeGdj (B: s (3OQGSI bGfhfjI ebGQfI (B/ s - (3eMeO CMeO eJhdj ESeGYjd s; (3gGfj UdGM SQj GdOjf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2017)
(3de jcf EUOGQ dLfI HGRd deHGOFgG (B: (3OGdI UGQJ HeKGHI EWGQ ef CLd Jbjje QbGHI eUQajI aGYdjI (B: (3djVja GdJRGekG LOjOkG Edj CYHGA GdHfhc (B: (3hEfeG LGA aj GdebGe GdChd cNdGUI ZfjI ef CLd JWhjQ GdYed GdeUQaj heG hGLgg ef CReGJ (B: (3hcPdc ef CLd JMOjO bhGYO efJXeI jLH eQGYGJgG aj eNJda GdYedjGJ GdeUQajI dVeGf Mbhb GdCWQGa GdeJYGedI (B: (3hcPdc CjVkG dJaYjd OhQ GdCTQGa GdOGNdj hGdNGQLj ef NdGd HjGf UdGMjGJ GdeQGbHjf hVeGf GSJbdGdge djchf eQTOkG dYed GdEOGQI GdeUQajI(B. (3Ef GdMGLI Gdjhe JdM YdjfG Cf jchf gfGc QbGHI eUQajI aYGdI hefJXeI Jbhe Ydj CSS heHGOF eMOOI hObjbI CcKQ ef Cj hbJ eVj fJjLI ddJWhQ GdSQjY hRjGOI JYbjOGJgG hNUhUkG YbH EONGd JcfhdhLjG GdeYdheGJ Edj eNJda CfTWJgG (B. (3Ef gPg GdOQGSI gj eMGhdI LGOI dSHQ CZhGQ eHGOF HGRd djS abW ef GdfGMjI GdfXQjI (B: (3hEfeG ef GdfGMjI GdYedjI GdJWHjbjI (B: (3ef CLd age CYeb dcjajI JMbjb SdGeI GdYed GdeUQaj (B: (3hJLfH GdeNGWQ GdeMJedI GdJj JhGLggG GdeUGQa heOj EecGfjI GSJNdGU UjGZI QbGHjI eJhGabI eY WHjYI Yed GdeUGQa GdYQHjI hVeGf SdGeJgG s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj (B2017.s
(3HHdjhLQGajG(B: (3UaMGJ (B363-383.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3gjcd GdLgGR GdeUQajs; (3GJaGbjI GdLGJs; (3GdeNGWQ GdeUQajIs; (3eYGjjQ GdGaUGM hGdTaGajIs; (3bGfhf GdHfhc GdeUQjs; (3MhceI GdTQcGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs